PERMODELAN PROTOTYPE E-KATALOG SEBAGAI MEDIA PEMASARAN BAGI PELAKU UMKM TENUN KRE' ALANG SUMBAWA - Ekastini; Nora Dery Sofya; Eki Ruskartina; Elita Trisyawidia; Bintang Bintang; Erwin Martadinata (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Kre’ Alang is a traditional woven fabric unique to Sumbawa that holds high cultural and economic value, beauty, and uniqueness, attracting many people. The competition between authentic Kre’ Alang from Sumbawa and similar imitation products that are cheaper poses a threat to the existence of authentic Kre’ Alang. One of the factors causing authentic Kre’ Alang from Sumbawa to struggle against imitation products is the limited marketing media available. UMKM players in Sumbawa still rely on word-of-mouth marketing to promote Kre’ Alang products, which limits their ability to reach a broader market. This has resulted in the original Kre’ Alang from Sumbawa not being able to fully realize its market potential. The e-catalog is a solution that can help reach a wider market. The e-catalog provides complete and detailed information about products to consumers, making it easier to choose and purchase the desired products. Research conducted in 2023 by a team of researchers shows that technology orientation is an important factor in enhancing product competitiveness. Technology orientation refers to the level of use of the latest technology in product marketing. The use of technology such as e-catalogs can help MSME actors like Kre’ Alang to market their products widely, thereby increasing competitiveness and opportunities to reach the market. The method for creating the Kre Alang e-Catalog prototype model uses a flexible prototyping method that is quick and dynamic in its development.